Electrocrystallization Regulation Enabled Stacked Hexagonal Platelet Growth toward Highly Reversible Zinc Anodes. (1st February 2023) - Shen, Zeyu; Mao, Jiale; Yu, Guoping; Zhang, Weidong; Mao, Shulan; Zhong, Wei; Cheng, Hao; Guo, Junze; Zhang, Jiahui; Lu, Yingying
Abstract: Realizing durative flattened and dendrite‐free zinc (Zn) metal configuration is the key to resolving premature battery failure caused by the internal short circuit, which is highly determined by the crystal growth in the electrocrystallization process. Herein, we report that regulating the molecular structure of the inner Helmholtz plane (HIP) can effectively convert the deposition into activation control by weakening the solvated ion adsorption at the interface. The moderated electrochemical reaction kinetics lower than the adatom self‐diffusion rate steers conformal stratiform Zn growth and dominant Zn (0001) texture, achieving crystallographic optimization. Through in situ mediation of electrolyte engineering, orientational plating and stripping behaviors at edge‐sites and tailored solvation structure immensely improve the utilization efficiency and total charge passed of Zn metal, even under extreme conditions, including high areal capacity (3 mAh cm −2 ) and wide temperature range (−40–60 °C). Abstract : A control mechanism of electrolyte on zinc electrocrystallization is proposed and validated through cyclic and linear sulfone cosolvents. The inner Helmholtz plane (IHP) formed by vertical dipole array is able to convert the deposition into activation control by weakening the solvated ion adsorption at the interface, steering conformal stratiform Zn growth and preferred orientation of Zn electrocrystallization.